2021
DOI: 10.1021/acs.jafc.1c01312
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid Metabolism in Astringent and Nonastringent Persimmon (Diospyros kaki) Cultivars Determines Sensitivity to Alternaria Infection

Abstract: Fruits of nonastringent persimmon cultivars, as compared to astringent ones, were more resistant to Alternaria infection despite having lower polyphenol content. Metabolic analysis from the pulp of nonastringent “Shinshu”, as compared to the astringent “Triumph”, revealed a higher concentration of salicylic, coumaric, quinic, 5- o -feruloyl quinic, ferulic acids, β-glucogallin, gallocatechin, catechin, and procyanidins. Selected compounds like salicylic, ferulic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Ferulic acid inhibited the growth of F. oxysporum at high concentrations and affected the activity of hydrolases associated with pathogenicity ( Wu et al, 2010 ). Ferulic and rho-coumaric acids reduced Alternaria growth in vivo and black spot in stored fruits ( Yadav et al, 2021 ). Ferulic acid leads to irreversible changes in cell membrane properties (charge, intracellular and extracellular permeability, and physicochemical properties) through hydrophobicity changes, reduction in negative surface charges, and local rupture of the cell membrane or pore formation, resulting in the leakage of essential intracellular components of pathogenic bacteria ( Borges et al, 2013 ).…”
Section: Hcaas Pathway Is Involved In Plant Disease Resistancementioning
confidence: 99%
“…Ferulic acid inhibited the growth of F. oxysporum at high concentrations and affected the activity of hydrolases associated with pathogenicity ( Wu et al, 2010 ). Ferulic and rho-coumaric acids reduced Alternaria growth in vivo and black spot in stored fruits ( Yadav et al, 2021 ). Ferulic acid leads to irreversible changes in cell membrane properties (charge, intracellular and extracellular permeability, and physicochemical properties) through hydrophobicity changes, reduction in negative surface charges, and local rupture of the cell membrane or pore formation, resulting in the leakage of essential intracellular components of pathogenic bacteria ( Borges et al, 2013 ).…”
Section: Hcaas Pathway Is Involved In Plant Disease Resistancementioning
confidence: 99%
“…As of now, it is not clear if all these traits (astringency, high firmness, and low susceptibility to Alternaria ) are related to each other and resulted from a pleiotropic effect, caused by a parallel changes in the pathways/compounds in the non-astringent cultivars leading to non-astringency. In our previous study, we suggested that phenolic compounds in non-astringent cultivars contribute to A. alternata resistance ( Yadav et al, 2021a ), but it is not clear if these compounds are also affecting the other traits. Alternatively, the mutation causing non-astringency can cause a defect in an upstream component, which might affect many non-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact genetic modification responsible for the non-astringent phenotype within the AST locus has not been identified. This genetic modification reduced the accumulation of polyphenols and condensed tannins ( Yadav et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal diseases caused by pathogenic fungi generate the severe losses of yield and economics all over the world. Alternaria alternata (A. alternata) is the primary cause for the black spot disease (BSD) of agricultural products, which has been reported to infect various fruits, including jujube, apple, citrus, pear, and plum. During the preharvest and postharvest stages, these fruits can be easily infected by A. alternata, leading to severe rot and spoilage.…”
Section: Introductionmentioning
confidence: 99%